Design and optimization of the seedling needle and push device for a mechanical transplanter of seedlings from bowl-type trays made of paddy straw - Li, Lianhao; Zhu, Chenhui; Liu, Bingxu; Li, Donghao; Lyu, Zhijun; Xu, Lianchao; Huang, Huinan (International Journal of Agricultural and Biological Engineering, 2025)
To meet the operational criteria for mechanical transplanting of young seedlings in paddy-straw-made bowl-seedling trays, a new seedling needle and seedling pushing device have been developed. This paper presents the design process and analyzes the effects of key parameters, including the angle of inclination of flat edge, width of flat edge, length of flat edge, wedge angle, and width of seedling pushing device for new seedling needle and seedling pushing device. Optimization parameters of new seedling needle and seedling pushing device have been validated by orthogonal experiments. The optimized values, such as a flat edge inclination angle of 35°, a flat edge width of 10 mm, a flat edge length of 64 mm, a wedge angle of 60°, and a seedling-pushing device width of 8 mm, satisfy the operational requirements for mechanically transplanting young seedlings in paddy-straw-made bowl seedling trays. The results demonstrate significant improvements in transplanting efficiency within Chinese agricultural systems. Key words: paddy-straw-made bowl-seedling trays; mechanical transplanting work; seedling needle; seedling pushing device; optimization DOI: 10.25165/j.ijabe.20251806.9812 Citation: Li L H, Zhu C H, Liu B X, Li D H, Lyu Z, Xu L C, et al. Design and optimization of the seedling needle and push device for a mechanical transplanter of seedlings from bowl-type trays made of paddy straw. Int J Agric & Biol Eng, 2025; 18(6): 75–82.